Adaptive migration: pluralising the debate on climate change and migration. Issue 4 (6th November 2017) - Baldwin, Andrew; Fornalé, Elisa
Abstract : The interaction between environmental change and human mobility is attracting global attention, both in policy circles and in the contemporary literature. This introductory essay proposes using the concept of pluralism to explore the multi‐dimensional relationship between climate change and migration and to advance new perspectives and concepts to interpret the emerging theory of adaptive migration. The papers included in this themed section cover diverse issues in this area of research by focusing on the contemporary debate about the 'migration‐as‐adaptation strategy'. The papers address six key areas: the role of law in dealing with climate‐induced migration, the category of place related to the community of origin and destination, the theme of climate justice and rights, the contribution of international organisations in framing the migration‐as‐adaptation strategy, adaptive measures developed in the Maldives, and seasonal nomadism in the East Sudan. All are quite different, but all converge in their emphasis on the role of the individual, the migrant, and on whether and how state responses are adequate in the progressive concordance between adaptation and individual capability. This introduction raises a set of salient questions that might catalyse multiple new research trajectories over the coming years.